2021
DOI: 10.1109/lra.2021.3101519
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Undulation of the Bendable Body of a Gecko-Inspired Robot for Energy-Efficient Inclined Surface Climbing

Abstract: Sprawling posture animals with their bendable spine, such as salamanders, and geckos, can perform agile and versatile locomotion including walking, swimming, and climbing. Therefore, several roboticists have used them as templates for robot designs to investigate and generate efficient locomotion. Typically, walking and/or swimming abilities are realized by salamander-inspired robots with a bendable body, whereas climbing ability is achieved on gecko-inspired robots with an oversimplified fixed body. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The body motion and gait pattern also influence the tail design. A robot with a bendable body (Haomachai et al (2021)) may need a soft or lateral undulating tail to compensate for the body swing. A robot with a lizard-like gait pattern (raising two legs at the same time) (Shao et al (2022)) can benefit from a tail that provides a substantial preload or functions as additional support for stable slope climbing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body motion and gait pattern also influence the tail design. A robot with a bendable body (Haomachai et al (2021)) may need a soft or lateral undulating tail to compensate for the body swing. A robot with a lizard-like gait pattern (raising two legs at the same time) (Shao et al (2022)) can benefit from a tail that provides a substantial preload or functions as additional support for stable slope climbing.…”
Section: Discussionmentioning
confidence: 99%
“…et al (2021)), have been extensively studied. Hence, geckoinspired climbing robots (Menon et al (2004); Unver et al (2006); Kim et al (2008); Jusufi et al (2008Jusufi et al ( , 2010Jusufi et al ( , 2011; Estrada et al (2014); Haomachai et al (2021); Shao et al (2022)) and dry adhesive materials (Murphy et al (2009); Bartlett et al (2012); Glick et al (2018); Suthisomboon et al (2021)) have rapidly been developed. They can adapt to different substrate surfaces (Kim et al (2008)) and even carry 100x their own weight (e.g., 9g climber (Hawkes et al (2015))).…”
Section: Introductionmentioning
confidence: 99%
“…Inchworm gait that extends and bends body sequentially is mimicked to allow a small soft robot to climb up on a pole [8]. The gecko in-plane bending movement is replicated in Slalom [14], which has reduced energy consumption in climbing by half compared to the rigid body on 30 • slope, equivalent to 0.5 Earth's gravity (0.5 G).…”
Section: B Body Linkage Mechanismmentioning
confidence: 99%
“…Grippers for climbing can be categorized by if there is explicit grasping, such as with fingers or not. Magnetic [18] or suction-based [19] end effectors, dry adhesive toes such as a gecko gripper [7], and EPDM Rubber [14] are other viable options for climbing robots. LEMUR 2B [2] has demonstrated a bouldering wall climbing by hocking a high-friction rubber wrapped end-effectors.…”
Section: Climbing Grippers and Spine Tipsmentioning
confidence: 99%
“…In 2000, AUTUMN et al [ 16 ] revealed the adhesion characteristics and mechanism of the gecko’s feet. In the past 20 years, the research on dry adhesion climbing robots has made great progress.…”
Section: Introductionmentioning
confidence: 99%